Analisis Tingkat Kesehatan dengan Metode RGEC pada PT. Bank Negara Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the health level of PT. Bank Negara Indonesia using the RGEC method.(Risk Profile, Good Corporate Governance, Earnings, Capital)This study uses a quantitative research approach with a descriptive approach. Data were obtained through observation and documentation at PT. Bank Negara Indonesia. The data analysis technique used in this study was the RGEC method.(Risk Profile, Good Corporate Governance, Earnings, Capital)The results of this study indicate that the quality of composite risk management implementation is quite adequate, the implementation of GCG principles is well-executed, the company's management capabilities from the profitability factor are adequate and support capital growth, and PT. Bank Negara Indonesia is able to manage the company's capital very well.Risk Profileshows that the quality of composite risk management implementation is sufficient. Profitability Assessment (Earnings) at Bank Negara Indonesia using two ratios, namely ROA and NIM during 2020-2024, shows that the company's management capabilities from the profitability factor are adequate and support capital growth. Capital Assessment (Capital) at Bank Negara Indonesia was in very healthy condition from 2020 to 2024. This indicates that the bank managed its capital very well during that period.